VRAC channel inhibition as a novel strategy for the treatment of ischemia-reperfusion injury - Gao, Yuhan; Li, Lu; Zhang, Yuejun; Chu, Yanlong; Han, Guang (Frontiers in Cell and Developmental Biology, 2024)
Ischemia-reperfusion injury is a serious clinical pathology involving multiple organs such as the heart and brain. The injury results from oxidative stress, inflammatory response and cell death triggered by restoring tissue blood flow after ischemia, leading to severe cell and tissue damage. In recent years, the volume-regulated anion channel (VRAC) has gained attention as an important membrane protein complex. VRAC plays a dual role in ischemia-reperfusion injury: on the one hand, activated VRAC promotes the release of intracellular chloride and glutamate, exacerbating cellular swelling and excitotoxicity, and on the other hand, the regulatory effect of VRAC may also provide protection to cardiomyocytes. This article reviews the pathophysiological mechanisms of ischemia-reperfusion injury, existing therapeutic strategies and their limitations, focuses on the molecular structure of VRAC, its activation mechanism, and its role in ischemia-reperfusion injury, and concludes with a discussion of the potential of targeted inhibition of VRAC as an emerging therapeutic strategy and the challenges it faces. A deeper understanding of the role of VRAC in ischemia-reperfusion injury is expected to provide new therapeutic ideas to improve patient prognosis.